Study on the adsorption of pb(ii) onto citric acid and monosodium glutamate modified rubber leaf powder / Ahmad Faisal Fadzil - Fadzil, Ahmad Faisal (2014)
To date, studies related to natural adsorbents were found to show promising potential as an alternative to current wastewater treatment methods. Most of the studies were found to center on the modified natural adsorbents as an alternative to activated carbon. However, little study has been done to explore the influence of modification of natural adsorbents using organic acids. This research attempts to fill in this knowledge gap by studying the influence and performance of citric acid and monosodium glutamate modified rubber leaf powder. Three main components of this study are the characterisation of modified adsorbents regarding their physicochemical properties; the adsorptive performance of the adsorbents in treating Pb(II) from aqueous solutions; and non-linear mathematical modelling on the adsorption data. Pb(II) adsorption studies were investigated under batch and fixed bed column modes. The results emerge to suggest that the amount of Pb(II) adsorbed increased with increasing pH, contact time, initial Pb(II) concentration, adsorbent dosage and temperature for for citric acid modifed rubber leaf powder (CARL) and monosodium glutamate modified rubber leaf powder (MGRL). The adsorption data suggests that the kinetics of Pb(II) adsorption by CARL and MGRL fits well with pseudo-second order model. This model theorises that chemisorption could be the rate determining step for Pb(II) adsorption. The equilibrium time was achieved within 90 min for CARL and MGRL. Adsorption of Pb(II) followed the Langmuir isotherm model for MGRL with the monolayer adsorption capacities of 125.82 mg/g. The qmax achieved by CARL was 97.19 mg/g. The optimum adsorption process occurred at pH 4. Possible mechanisms involved in the Pb(II) adsorption by CARL and MGRL were mainly physical adsorption and chemical adsorption, respectively. The findings from the FTIR spectra and Dubinin-Radushkevic isotherm model investigation supports the mechanism suggested. For both adsorbents, the rate limiting step is chemisorption. Fixed bed column data were in good agreement with the Thomas which predicts the maximum adsorption capacity and breakthrough curve and Yoon-Nelson model which predicts the service life of a column. The maximum adsorption capacity for the columns were 37.70 to 48.70 mg/g for CARL and 51.28 to 75.76 mg/g for MGRL. From both batch and fixed bed column studies, MGRL proved superior to CARL by having higher maximum adsorption capacities and longer service life.